A literature-based intervention for women prisoners: preliminary findings. Issue 4 (19th December 2016) - Billington, Josie; Longden, Eleanor; Robinson, Jude
Abstract : Purpose: The purpose of this paper is to investigate whether Shared Reading (SR), a specific literature-based intervention, is transposable to a prison context and whether mental health benefits identified in other custodial and non-custodial settings were reported by women prisoners. Design/methodology/approach: In all, 35 participants were recruited within an all-female maximum security prison and attended one of two weekly reading groups. Qualitative data were collected through researcher observation of the reading groups; interviews and focus group discussions with participants and prison staff; interviews with the project worker leading the reading groups; and a review of records kept by the latter during group sessions. Findings: Attendance rates were good, with nearly half of the participants voluntarily present at =60 per cent of sessions. Two intrinsic psychological processes associated with the SR experience were provisionally identified, "memory and continuities" and "mentalisation", both of which have therapeutic implications for the treatment of conditions like depression and personality disorder. Research limitations/implications: Limitations included the small sample, lack of control for confounding variables, and constraints imposed on data collection by the custodial setting. Originality/value: Although more controlled research is required, the findings indicate that women prisoners will voluntarily engage with SR if given appropriate support, and that the intervention has potential to augment psychological processes that are associated with increased well-being.